IDENTIFIKASI ELEMEN PEMBENTUK IDENTITAS JALAN MALIOBORO YOGYAKARTA TINJAUAN DARI PERSEPSI MASYARAKAT - , ARNIES FASYA MEININDA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the past, Malioboro is the main place to gathering, hanging out, and expressing the creativity. However, in the recent time, the historical values of Malioboro formation and the surrounding environment have been replaced gradually due to the developing process of the city, which refer to liberalism. This case could lead Yogyakarta loss of identity in which this city has the special characteristic that cannot be found in any other cities. Based on this rationale, this study aims at giving contribution to formulate the elements that characterizes Malioboro Street. The public society plays crucial role to assess the elements of Malioboro character because their part as the âuserâ of Malioboro. The character or identity will be felt by visitors who are not exploiting Malioboro in their everyday life because they will judge based on their observations during their visit, their past memory, and any different experiences among people from one another. Retrieval of data through questionnaire distribution to the general public consists of two stages. The first phase of data collection involved 20 community respondents domicile Yogyakarta and 20 community respondents outside Yogyakarta. The results of the first phase used for the second phase of data collection with the same number of respondents, but with different people. From the analysisi of the second phase of data collection obtained elements of Beringharjo Market, Vredeburg Castle, and Gedung Agung (Presidential Palace of Yogyakarta), street lights, andong, becak, the trading activities of the souvenir-street vendors, and the public activities in front of Vredeburg Castle as Malioboro identity according to the public society. These elements could be the fundamental direction of the designing order to strengthen the character of Malioboro Street to be consistent. Keywords: special characteristic, identity, character, Malioboro